Aesthetic Correction of Gynecomastia with Liposuction and Limited Access Breast Excision – an Experience - Alhotan, Saleh; Salati, Sajad Ahmad (Lietuvos chirurgija, 2025)
Background. Gynecomastia is the most common breast disorder in males and is characterized by benign enlargement of glandular tissue. Surgical management options are adopted if it fails to resolve spontaneously or if conservative measures are ineffective in alleviating symptoms. Liposuction with limited access mammary gland excision is one such option. Aim of the study. This study was undertaken to study the outcomes of gynecomastia treated with liposuction and limited access mammary gland excision. Methods. The data related to the patients was analysed retrospectively and multiple variables were studied which included the demographics, grading, complications, and patient satisfaction. Results. 85.4% of patients were highly satisfied or satisfied with the outcomes, and 78.9% witnessed significant improvement in psychosocial distress. Minor complications were recorded in 35.4% of cases, and histopathological analysis of retrieved breast tissue specimens revealed benign features in all the patients. Conclusions. There are several surgical treatments for managing gynecomastia that either fails to resolve spontaneously or causes distressing symptoms. Liposuction with limited access mammary gland excision is one such option and is highly successful.